Disturbance Attraction Domain Estimation for Saturated Markov Jump Systems with Truncated Gaussian Process - Liu, Y.; Yin, Y.; Liu, F.; Teo, Kok Lay (Gordon and Breach, 2014)
This paper investigates the disturbance attraction domain estimation of saturated Markov jump systems with truncated Gaussian process. The aim is to estimate the disturbance domain of attraction so that the state is maintained in a neighbour around the origin by a state feedback controller regardless of bounded disturbance. The problem is formulated as parameter-dependent linear matrix inequalities (LMIs). The optimal disturbance attraction domain is obtained through searching for most appropriate auxiliary parameters in the defined domain. A numerical example is presented to show the potential application of the results.